Examination of the concept and implementation of the programs individually oriented physical education students - Belykh S. I. (Kharkov National Pedagogical University, 2013)
The aim of the work is the examination of concepts and programs for student-centered physical education students. The experiment included 20 experts. It is shown that the existing approach to training in "Physical Education" in higher educational establishments of sports profile do not solve the problems of improving the quality of training of future specialists. It is proved that the model of personality-oriented physical education has obvious advantages. Substantiated scientific and methodical conditions improving the training of future specialists of physical education for a healthy way of life. The level of the developed concepts and programs individually oriented physical education has allowed experts to make a competent judgment on the benefits of this approach.